IMPLEMENTASI FUNGSI-FUNGSI MANAJEMEN KEPALA MADRASAH UNTUK MENINGKATKAN MUTU PEMBELAJARAN GURU DI MTS NURUL IMAN - Kartika Sari Siagian (Universitas Islam Negeri Sumatera Utara Medan, 2018)
This study aims to describe: Implementation of Principal Management Functionsto Improve Teacher Learning Quality at Mts Nurul Iman Tanjung Morawa. This research was conducted at Mts Nurul Iman Tanjung Morawa Jl. Pasar XIII Kelurahan Limau Manis Tj. Morawa, Deli Serdang Regency. The approach in this study is a descriptive approach. As informants in this study were principals, vice principals and teachers. Data collection techniques used in this study were interviews, observation, and documentation. Data analysis is done by reducing data, presenting data, and drawing conclusions. While testing the validity of the data is done by means of credibility, transferability, dependability, and confirmability. In conducting this research the researcher chose the type of qualitative research, a qualitative approach. To obtain data the author conducted interviews, observation, documentation and test the validity of the data. Based on the results of this study, it can be concluded that the application of the management functions of the principal at Mts Nurul Iman Tanjung Morawa is good, as evidenced by the fulfillment of all activities in the process of implementing the function function of the Principal's management. Broadly speaking there are two factors that influence the quality of learning, including: 1) Supporting factors that include, the leadership of the principal, coordination and cooperation as well as the skills of the teacher in managing the class, 2) The inhibiting factors include, facilities and infrastructure, budget or education funding and the low quality of educators. The implication of this research is that the application of management functions in improving the quality of learning must be conditioned by the school budget and strategic concepts as anticipation of the inhibiting factors that can drain time and educators such as teachers and other education personnel.Keyword: Management Functions of Madrasah Heads, Learning Quality